Investigation the links between foreign investment, economic growth and energy usage: Organization of the Islamic Conference Countries - Gamoori, Asma; Jorjorzadeh, Alireza; Mehrabani, Fatemeh (International Journal of Energy Economics and Policy, 2017)
The vital importance of energy on one hand and its scarcity on the other hand requires the greater attention of the economic activists to use make a more efficient use of this production factor. Due to the difference between various energy resources as well as different performance of countries in using energy resources from technical and technological viewpoint, the investigation of the relationship between energy consumption and macroeconomic variables especially in Islamic countries is an outstanding issue. The purpose of the current study was to investigate the relationship between foreign investment, financial development and foreign trade with energy consumption member countries of the Organization of the Islamic Conference during the period of 2000-2014 using panel data approach. The results of the study indicated that foreign trade, investment and financial development had a positive significant effect on the energy consumption in the studied countries. Moreover, the greatest effect was attributed to the foreign trade. Keywords: foreign trade, foreign investment and financial development, energy consumption, Islamic countries. JEL Classifications: F0; O5